Dynamic Spatial-temporal Evaluations of Urban Heat Islands and Thermal Comfort of a Complex Urban District Using an Urban Canopy Model. Issue 3 (1st September 2016) - Liu, Lin; Lin, Yaoyu; Wang, Dan; Liu, Jing
Abstract : This study conducted hourly dynamic simulations of the thermal climate and thermal comfort of 120 blocks within the complex district of the International Low Carbon City (ILCC) by applying an urban energy balance model (UDC), during the summertime in Shenzhen. Two parameters, including the local urban heat island (LUHI) and SET*, were adopted as evaluation indices, and the temporal-spatial distributions of these parameters were discussed. The results show that the northeast blocks of the ILCC always presented higher values of LUHI and SET* compared with the lower values of the middle blocks. The LUHI values varied between different blocks at the same time, ranging between -4°C and 4°C, whereas the SET* values varied from 27.5°C to 33.5°C. The large differences in the LUHI and SET* values between these blocks may be caused by their different urban spatial patterns and the varied underlying surface compositions. Additionally, the average diurnal variation of LUHI showed more fluctuations compared with the continuous conic variation manner of SET*. The average maximum values of LUHI and SET* both occurred in the afternoon, whereas the average minimum values occurred in the early morning.